The Digitalizing Women’s Social Capital: Community-Based Communication and Gendered Agency in Rural Food Systems - Farida Nurul Rahmawati; Nikmah Suryandari; Netty Dyah Kurniasari; Ferry Adhidarma (Jogjakarta Communication Conference (JCC), 2026)
This research examines communication practices in community-based organisations to increase women's and family health social capital through food diversification in rural communities, especially in Madura, Indonesia. The analysis focuses on the role of traditional women’s networks in communication for development approaches and on how they are increasingly harvested for specific purposes and integrated into institutions through various digital platforms, such as WhatsApp groups. This hybridisation enables collective learning, increases nutritional awareness and assists in negotiating household food decisions within a patriarchal cultural milieu. The data, surveys and interviews were recorded in Sumenep and Pamekasan. Results indicate that while women maintain strong social networks and relationships in their communities, they typically lack formal authority over household food expenditures. By transmitting information and fostering a sense of togetherness, digital community communication empowers women to reach out to their peers. As a result, women are able to champion local foods such as corn, tubers and traditional spices as desirable nutritious substitutes for rice. This study integrates participatory communication (Middleton) and persuasive communication (Yale Model) lines of research to propose a community-centred digital communication platform framework. This framework leverages social capital to facilitate gendered agency in rural development. The study offers an innovative perspective by framing “digitalised social capital” not merely as technology adoption but as a hybrid communication system that disrupts collective norms and household food management. This study contributes to the Sustainable Development Goals SDG 2 (Zero Hunger), SDG 3 (Good Health and Well-being), SDG 5 (Gender Equality) and SDG 17 (Partnerships for the Goals) as localised digital communication interwoven within women’s community networks can improve food security resilience and gender-inclusive development for rural South & Southeast Asian communities.